Effect of Reinforcement with Micro- and Ultradispersed Diamond Powders on the Properties of Diamond Tubular Drills During the Processing of Some Non-Metallic Materials - Umansky, V.P.; Krasovsky, V.P.; Bashchenko, O.A. (Powder metallurgy and metal ceramics, 2021)
The study presents the results of comparative laboratory tests of diamond tubular drills when drilling window glass, granite, and abrasive stones based on silicon carbide SiC. The tests were carried out in cold running water. Tin bronze containing micro- and ultradispersed diamond powders of ASM 40/28, ASM 10/7 (MDP), ASM 1/0 (UDDP) grades, and molybdenum powder were used as a matrix of the tool. Furthermore, the dependence of the hardness of specially prepared matrix samples on their composition was examined. With an increase in the ASM 1/0 concentration up to 5 wt.% in the reinforcement, the hardness of the matrix samples increased by one-third and reached a maximum of ~96.5 HRB. A further increase in the ASM 1/0 concentration led to a slight decrease in the hardness of the samples. The use of larger diamond powders required a higher concentration, providing high values of hardness. By adding ASM 10/7 in an amount of 10 wt.% and ASM 40/28 in the amount of 40–60 wt.% we managed to increase the hardness of the matrix to the same maximum. The introduction of a reinforcement in a bonding matrix of diamond tubular drills in amount ensuring its maximum hardness has significantly increased the efficiency of their operation. Thus, the wear of drills after glass processing decreased by 2–6 times, and the drilling speed increased by 3–4 times. Drill wear after granite processing has decreased by 50–84 times, and the drilling speed has increased 2.7–6 times, correspondingly. Finally, after processing of an abrasive stone based on silicon carbide SiC, the wear of diamond tubular drills decreased by 1.4– 2.9 times, and the drilling speed increased by 1.5–2.5 times. The effect of additives in the reinforcement of the tool depended on the choice of the diamond powder grade and their concentration. The best option was the introduction of ASM 1/0 (UDDP) powder in an amount of 5– 9 wt.%. The introduction of ASM 10/7, and especially ASM 40/28 (MDP), into the reinforcement required, firstly, their higher concentration (10–40 wt.%), and secondly, was not effective enough since the wear indicators of diamond tools were higher, and the drilling speed was lower.